Valorization of groundnut haulms in the feeding of small ruminants in the Sudanian area of Benin. - AHOUNOU, GBÊNAGNON SERGE; AGBOKOUNOU, ARISTIDE MAHOUTIN; DAHOUDA, MOHAMADOU; Moutouama, Victor; DJENONTIN, Jonas André; MENSAH, Guy A.; KOUTINHOUIN, G. BENOÎT; HORNICK, Jean-Luc; YOUSSAO, ALASSANE (My University, 2017)
Groundnut haulms are highly used in the feed of ruminants in Benin. This study was conducted to characterize practices related to the incorporation of groundnut haulms in the feed of small ruminants in the Sudanianarea of Benin. A total of 113 small ruminants keepers were interviewed in Borgou and Alibori Departments of the country. The study revealed that interviewed famers belong to diverse ethnic groups mainly Bariba (52.2%), Dendi (12.4%) and Gando (5.31%). The proportions of the other ethnic groups (Fon, Ottamari, Lokpa, Mokole, Nago, Peulh, Ubiore, Djerma and Yom) were very low and varied from 3.54% to 1.77%. The use of groundnut haulms in the feed of small ruminants is mostly practised by male farmers (83.2%). About 92.8% of respondents were married. Most of those who use groundnut haulms harvest them from their own farms (65.5%), while others (31.0%) receive them as gifts, and some (27.4%) purchase them from producers. The majority of breeders (98.2%) use groundnut haulms to feed sheep. Many respondents (77.0%) reported that groundnut haulms are used in the dry season, whereas 29.4% use it whenever it’s available. The present study indicates the need for improving practices of groundnut haulms use in the feeds of small ruminants among breeders.
Keywords: Arachishypogeae; Breeders; Benin; North; Sheep